The effect of Teucrium polium consumption and resistance training on the lipid profile of military staff - Ehsan Roostaii-darehmyaneh; Farah Nameni (فصلنامه ابن سینا, 2020)
Background: Effectiveness of simultaneous exercises and the use of herbal supplements on metabolism can be helpful. In this study, the effects of Teucrium polium and resistance training on the lipid profiles of military staff have been investigated. Materials and methods: This research was performed quasi-experimentally with pre-test and post-test design in two groups) with and without the use of Teucrium polium). Twenty individuals were randomly selected from the staff of one of armed forces in Iran. Subjects in one group consumed Teucrium polium and dextrose (125 mg per day).Then, the resistance training program was done jointly by the two groups (for eight weeks). Blood samples were taken at two intervals just before the first of the study and immediately after the last training session, and results were statistically analyzed. Results: The results of this study showed that the mean blood lipid profile was increased, although, it was not significant in one-way analysis of variance. Only changes in HDL had a significant increase. Conclusion: The lack of effect of Teucrium polium on lipid profile can be due to the release of stored fats in the body and their mobilization to enter the energy production stream. The increase in HDL may be due to the increased endogenous secretion of testosterone as a result of resistance training and the principle of overload and its amplification by teat. Therefore, a regular long-term exercise with increased lipoprotein lipase levels and accelerated degradation of triglyceride-rich lipoproteins has increased the transfer of surface compounds.